Negotiating Sacred Law: Qur’anic Hermeneutics, Legal Pluralism, and Interfaith Marriage in Muslim-Majority Countries - Syarif Syarif; Saifuddin Herlambang; Budiyono Budiyono; Gama Pratama; Fharkhan Luthfi; Nur Paikah (Universitas Islam Negeri Antasari Banjarmasin, 2025)
Interfaith marriage remains a persistently contested legal issue in Muslim-majority societies, situated at the intersection of Islamic legal authority, state constitutional frameworks, and global human rights discourses. The complexity of this debate has intensified within the context of the modern nation-state, which manages religious pluralism through state law and bureaucratic governance. This article examines how marital norms within Islamic law are not only formulated at the normative level but also negotiated, reinterpreted, and enacted within contemporary regimes of legal pluralism. Employing a qualitative approach grounded in an interdisciplinary framework, the study integrates doctrinal legal analysis, Qur’anic hermeneutics, and cross-national comparative law. Primary data are drawn from regulations and legal practices governing interfaith marriage in Indonesia, Egypt, Malaysia, and Turkey, while secondary data consist of classical fiqh (Islamic jurisprudence) literature, Qur’anic exegetical works, and relevant contemporary scholarship. The findings reveal a spectrum of regulatory models ranging from absolute prohibition and ambiguous tolerance to hybrid regulation and secular permission, shaped by the complex interaction of fiqh doctrines, state bureaucratic governance, and social dynamics. The study further highlights the strategic role of bureaucratic actors in producing what is termed pragmatic fiqh, as well as the transnational strategies employed by interfaith couples to navigate restrictive domestic legal frameworks. Theoretically, the article introduces the concepts of negotiated orthodoxy and fiqh pragmatism as analytical tools for understanding the adaptation and transformation of Islamic law in modern contexts. In doing so, the study contributes to contemporary debates on Islamic legal pluralism by advancing fiqh pragmatism as an adaptive paradigm that bridges sacred norms and modern social realities.